The influence of hydrocortisone on cellular defence mechanisms of Biomphalaria glabrata - Deborah Regina Serrano; Eliana Maria Zanotti-Magalhães; Luiz Augusto Magalhães; José Ferreira de Carvalho (Memorias do Instituto Oswaldo Cruz, 2002)
Since the internal defense system of mollusks consists of cellular and humoral mechanisms, we examined the role of hydrocortisone in mollusks defense cells and the influence of this steroid on the development of Schistosoma mansoni in its intermediary host. Hydrocortisone had an immunosuppressive action in Biomphalaria glabrata, as reflected in the reduced number of defense cells and the altered cell physiology. Histopathological analysis showed that hydrocortisone facilitated the intramolluscan development of S. mansoni, by reducing the extent of the inflammatory response, seen as a greater number of viable sporocysts with no surrounding hemocytes.